A new model of conceptual design based on Scientific Ontology and intentionality theory. Part II: The process model. (May 2015) - Chen, Yong; Zhao, Meng; Xie, Youbai; Zhang, Zhinan
Abstract : To address the logical incoherence issue related to existing design models, this paper employs the conceptual foundation developed before to establish a new process model of conceptual design, i.e., the Need-Function-Principle-System model, which elaborates a conceptual design process with five major stages, i.e., clarification, synthesis, embodiment, analysis and prediction. The new process model can explain how a need in the intentional world is transformed into a function and then into an abstract principle in the semi-objective world, and finally into a model system in the objective world. The conceptual design of a hair-drying system is employed to demonstrate the developed design model. A discussion demonstrates that our process model of conceptual design is more logically coherent than existing design models. Highlights: A new theoretical model of conceptual design, i.e., the NFPS model, is proposed. The NFPS model can transform an intentional description into an objective one. The NFPS model can explain how basic principles are synthesized in designing. The NFPS model can explain how various new functions are derived in designing.